Self-perpetuating Technologies Of Religious Synthesis: A Case Study Of Socio-political Developments And Religious Change In Singapore - C. Graham, Fabian (Penerbit Universiti Sains Malaysia (USM Press), 2016)
In Chinese communities in the Asia Pacific region, religion constitutes an integral element of Chinese cultural identity. However, in Singapore's ethnically mixed environment, religious synthesis is becoming increasingly common with Chinese vernacular religion integrating beliefs and practices from neighbouring ethnic groups. Government policy in Singapore on the management of ethnic groups has been shaped by the aspiration to construct a multicultural nationalistic state, inadvertently fuelling religious acculturation, appropriation, interpenetration, transfiguration, hybridisation and cultural borrowing between ethnic and religious groups. An analysis of the interrelationship between the socio-political and religious arenas highlights varied catalysts that trigger these "technologies of new religious synthesis," and provides illustrations of their fundamental role as "self-perpetuating mechanisms" in multi-faith religious landscapes.